PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) DENGAN MODEL DISCOVERY LEARNING (DL) PADA MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Ulvi Amella Shinta; Nursal Nursal; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Biodiversity materials are many abstract concepts for learners. Learners can only imagine what the teacher says when explaining, so that learners have different responses to the knowledge described by the teacher. In this material, learners tend to only memorize the material alone, so that feel bored in learning and learning passively. The purpose of this research is to Produce Quality of Student Work Sheet (LKPD) with Discovery Learning (DL) Model on Biodiversity Material at grade Xon Senior High School. This research was conducted in Biology Education Program FKIP UR and Senior High School (SMA Negeri 4 Pekanbaru). The research was conducted onApril 2017 until November 2017. The type of this research is Development Research referring to R & D research approachused the ADDIE Model. There are 3 LKPD developed. The instruments of data collection in this study are LKPD assessment / validation sheets, and response questionnaires. After LKPD was developed, validated by 5 validators and then the first tested on 12 students of Biology Education Program FKIP UR, and the second testedon 20 studentsThe validation result shows that the score of feasibility aspect of the contents of 3 LKPD developed is 3.43 categories is ‘very valid’, the average score of design aspect is 3.48 categories is ‘very valid’, and the pedagogical aspect score is 3.88 categories is ‘very valid’. The average score of all aspects of all three LKPD is 3.41 categories is very valid. The results of the test I showed the average score 3.50 with very ‘good’ category. The results of the second test showed the average score of 3.61 with very ‘good’ category. LKPD with Discovery Learning Model (DL) on biodiversity material in grade X SMA is qualified and feasible to use.Keywords : Development of Student Work Sheet Discovery Learning (DL), Biodiversity